PENGARUH AKTIVITAS PERLINDUNGAN KAKI TERHADAP SENSASI PROTEKSI DAN RANGE OF MOTION KAKI PADA PENDERITA DIBETES MELITUS TIPE 2 DENGAN NEUROPATI PERIFER - Istiroha Istiroha; Elyana Asnar STP; Harmayetty Harmayetty (Universitas Nahdlatul Ulama Surabaya, 2017)
The somatosensory deficit in diabetic peripheral neuropathy can include loss of movement perception at the ankle joint and loss of plantar cutaneous sensation. Foot protection activities can maintain balance and strength of the legs. The purpose of this study was to determine the effect of foot protection activity on foot sensation, ROM of ankle and 1st MTP joint in type 2 diabetes with peripheral neuropathy. This research used pretest-postest control group design. Subjects used are patients with type 2 diabetes outpatient in RSUD Ibnu Sina Gresik as many as 28 patients. The subjects of the treatment group were given foot protection activity for 30 minutes, 2 times each week for 4 weeks. The variables measured were sensation of protection, ROM of ankle and 1st MTP joint. The instruments used are Semmes-Weinstein Monofilament Test (SWMT) 10g and goniometer. After 4 weeks of treatment, paired t test showed an increase in foot protection sensation, ROM of ankle and 1st MTP joint in the treatment group with p value SWMT = 0,000, ROM of ankle dorsiflexion p = 0,005, plantarflextion ankle p = 0,006, ankle eversion p = 0.002, ankle inversion p = 0,000, 1st MTP flexion p = 0.009 and 1st MTP extension p = 0.002. The independent t test value of foot protection sensation, ROM of ankle and 1st MTP joint between treatment and control group also showed significant differences in treatment group than control group. This study shows the effect of foot protection activity on the sensation of foot protection and ROM of the foot joint so that it can be used as an alternative intervention to prevent diabetic foot ulcers either independently or in health services.